Fluoride effectiveness in high caries risk and medically complex Veterans. Issue 6 (19th July 2014) - Jurasic, M. Marianne; Gibson, Gretchen; Wehler, Carolyn J.; Nunn, Martha; Orner, Michelle B.; Nunez, Elizabeth; O'Toole, Terry G.; Jones, Judith A.
Abstract Background The Global Burden of Disease Study showed there was a 34.5% increase in years lived with disability due to dental caries from 1990 to 2010. With the aging of 76 million baby boomers, dental caries will continue to pose a significant challenge for older adults. Objective Test the effectiveness of prescription or professionally applied fluoride in the prevention of new dental restorations in a clinical setting where patients are medically compromised and more dentally impaired than the general population. Methods A retrospective cohort study, using multiple electronic databases within the Department of Veterans Affairs. Propensity scores were used to adjust for confounding by indication and logistic regression modeled the outcome and included all expected covariates. Results The study sample included 140 114 high caries risk Veterans with a mean of 3.4 physical comorbidities, 1.2 mental comorbidities, and 11 medication groups per patient. Patients who received clinical fluoride treatments had 17–20% decreased odds of requiring a restoration during the follow‐up period. Conclusions Prescription self‐applied or professionally applied fluoride provided either before or during an episode of care significantly reduced the likelihood of new restorations in high caries risk and medically compromised Veterans.